Clinical and functional evaluation of intramyocardial implantation of autologous bone marrow cells treated with erythropoietinduring the CAD surgery (6-month results) - A. V. Fomichev; A. M. Chernyavskiy; K. K. Gulyaeva; O. V. Poveschenko; A. P. Lykov; J. E. Kareva; S. M. Minin; N. A. Nikitin (Вестник трансплантологии и искусственных органов)
Aim. Clinical and functional evaluation of the implantation of autologous bone marrow cells treated with erythropoietin in laser channels during coronary bypass grafting in patients with end-stage coronary lesion.Materials and methods. 60 patients with coronary artery disease with diffuse and (or) distal right coronary artery disease were randomized into two groups: patients of group 1 (n = 30) underwent coronary bypass grafting, implantation of autologous bone marrow cells treated with erythropoietin in laser channels, patients of the 2nd group (n = 30) were operated with coronary bypass grafting of the left coronary artery system. Assessment of the clinical status, myocardial perfusion and contractility was performed initially, 6 months after the operation.Results. Six months after the operation, there was a more pronounced decrease in angina pectoris (CCS) in the main group compared to the control group, also we revealed a 6-minute walk test scores improvement. Based on two-stage scintigraphy (Tc99) in the main group before the surgical treatment, a rest perfusion defect was 8.5% [3.5, 18.5], a stress-induced perfusion defect – 7.0% [6.0, 12, 3]. In the control group, the rest defect was 9.1% [5.6, 12.4], the stress-induced perfusion defect was 7.3% [6.1, 8.7]. 6 months after surgery rest perfusion defect at the indirect revascularization group was 6.0% [2.5, 16.5] (p = 0.008), a stress-induced defect was 4.0% [1.5, 6.3] (p = 0.05). In the control group, the rest defect was 8.7% [5.3, 10.3], the stress-induced perfusion defect was 6.8% [5.3, 9.1] (p = 0.21). The results of scintigraphy with MIBG showed a left ventricle innervation defect (PID) significant decrease in the main group: initially 15.4% [14.2, 16.3], after 6 months 11.7% [9.3, 13, 2] (p = 0.045). In the control group, there was an unreliable decrease in PID: initially 14.3% [10.2, 17.3], after 6 months 13.8% [9.1, 14.2] (p = 0.14).Conclusion. Our preliminary results revealed more pronounced effect of the new indirect revascularization method expressed as in myocardial perfusion improve, myocardial sympathetic innervation restoration and clinical status improvement in comparison with control group.